Pulpa y pergamino de café. V. Absorción y retención de nitrógeno en terneros alimentados con raciones elaboradas con pulpa de café - Cabezas, Marco Tulio; González, Jorge Mario; Bressani, Ricardo (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Nitrogen balance data of male, young Holstein calves, weighing 22 kg, fed diets containing 0, 12, and 24 per cent of day dehydrated coffee pulp, are presented. These diets were administered for a total of 18 days, with an adaptation period of 8 days and two 5-day balance for quantitative collection of feces and urine. The results showed a significant decrease in the nitrogen retained by the animals as coffee pulp in their diet increased from 0 to 14 per cent. A considerable increase in urine output was also observed as the percentage of coffee pulp in the diet increased, as well as a tendency for food intake and nitrogen digestibility to decrease.